Formulation and Evaluation of Papaya Seed Extract Hydrogel (Carica Papaya L.) As Well as its Effectiveness in Repairing Incision Wounds in Mice (Mus Musculus) - Fathoanah Qiran Sakinah; Aliyah Aliyah; Yulia Yusrini Djabir (Green Publisher Indonesia, 2026)
Papaya seeds (Carica papaya L.) contain flavonoids, saponins, alkaloids, steroids, and tannins that have been proven effective in accelerating the wound healing process. This research aims to formulate hydrogel preparations from papaya seed extract and test their effectiveness in healing incision wounds in mice. This research is experimental in nature, involving the preparation of a papaya seed extract hydrogel with chitosan as a polymer and PEG 400 as a crosslinker. The papaya seed extract hydrogel was tested on mice (Mus musculus) across five treatment groups. Wound healing data were statistically analyzed using a repeated measures ANOVA test, and the physical evaluation of the hydrogel preparations was conducted descriptively. The results of the study showed that the papaya seed extract hydrogel met the requirements of the hydrogel preparation evaluation tests. The statistical test results indicated a significant effect on wound healing in male mice (p < 0.05). Based on the results obtained, the papaya seed extract hydrogel (Carica papaya L.) demonstrated the best incision wound healing effectiveness. In conclusion, papaya seed extract hydrogel, particularly at a 15% concentration, effectively accelerates incision wound healing in mice and meets the physical quality standards for topical hydrogel preparations, making it a promising natural-based wound dressing.